The Influence of KDR Genetic Variation on the Efficacy and Safety of Patients With Advanced NSCLC Receiving First-Line Bevacizumab Plus Chemotherapy Regimen. (31st May 2021) - Geng, Nan; Su, Jingwei; Liu, Zhikun; Ding, Cuimin; Xie, Shaonan; Hu, Wenxia
Objective: Angiogenesis plays an important role in the growth and metastasis of non-small cell lung cancer (NSCLC). Bevacizumab is a humanized monoclonal antibody that mainly acts on vascular endothelial growth factor A (VEGFA) . Kinase insert domain receptor (KDR) is the most important target of VEGFA . The aim of present study was to investigate the influence of KDR genetic variation on the efficacy and safety of patients with advanced NSCLC receiving first-line bevacizumab plus chemotherapy regimen. Methods: A total of 169 patients with advanced NSCLC who received bevacizumab combined with chemotherapy were recruited in this study. Clinical outcome of the regimens was evaluated in the hospital. Peripheral blood and biopsy tissue specimens of patients were collected for the genotyping of KDR genetic variation and KDR mRNA expression, respectively. The association between KDR genotype status and other variables were analyzed. Univariate analysis of genotype status and prognosis was implemented using the Kaplan-Meier survival analysis method. Multivariate Cox regression analysis was performed to adjust the confounding factors. Results: Of the polymorphisms analyzed, only V297 L was of clinical significance. The prevalence of V297 L among the study population were as follows: CC genotype 123 cases (72.8%), CT genotype 41 cases (24.3%), TT genotype 5 cases (2.9%). The minimum allele frequency is 0.15. The distribution frequencies of the 3 genotypes corresponded with Hardy-Weinberg equilibrium ( P = 0.489). Patients with TT and CT genotypes were merged in the subsequent comparison of clinical outcomes. The analysis of efficacy exhibited that the objective response rates (ORR) of patients with CC genotype and CT/TT genotypes were 52.8% and 47.8% ( P = 0.561), respectively. Prognosis indicated that the median progression free survival (PFS) of patients with CC genotype and CT/TT genotype were 8.9 and 5.5 months, respectively ( P = 0.006). The median OS of the 2 genotypes were 20.0 and 14.9 months, respectively ( P = 0.021). Adjusted in multivariate Cox regression analysis of PFS, CT/TT genotypes were an independent factor for PFS [hazard ratio (HR) = 1.59, P = 0.011). Safety profile according to genotype status of V297 L failed to find significant difference. Interestingly, the expression of KDR mRNA of patients with CT/TT genotype was significantly higher than that of patients with CC genotype in the 58 cancer tissue specimens ( P < 0.001). Conclusion: The clinical comes of patients with advanced NSCLC receiving first-line bevacizumab plus chemotherapy regimens might be impacted by polymorphism V297 L through mediating the mRNA expression of KDR .